Manajemen Integrasi Sains dan Tauhid dalam Kurikulum Madrasah: Studi Kasus di Madrasah Aliyah Al-Mumtazah - Saidina Saidina; Yuniar Yuniar; Mardiah Astuti; Ahmad Zainuri (Al-Munawwarah : Jurnal Pendidikan Islam, 2026)
The integration of science and tauhid in Islamic education involves not only relating scientific concepts to religious values but also managing such integration systematically within the madrasah curriculum. This study aims to analyze the management of a tauhid-integrated science curriculum at MA Al-Mumtazah Pedamaran, focusing on curriculum planning, implementation, evaluation, and the supporting and inhibiting factors influencing its implementation. The study employed a descriptive qualitative approach. Data were collected through semi-structured interviews, non-participant observation, and document analysis. Participants were purposively selected and included the head of the madrasah, the vice principal for curriculum affairs, science teachers, Islamic education teachers, and students. Data credibility was strengthened through source triangulation, technique triangulation, and member checking. Data were analyzed through data condensation, data display, and conclusion drawing and verification. The findings indicate that the integration of science and tauhid has become part of the madrasah’s educational orientation, although its translation into instructional planning and learning materials remains uneven. The implementation of integration is reflected in the connections established between scientific concepts, Islamic values, reflection, and students’ behavior. Evaluation is conducted through various forms of assessment and institutional monitoring, although the operational measurement of tauhid-related values remains challenging. The study demonstrates that science–tauhid integration should be managed as a continuous curricular process involving planning, professional collaboration, implementation, evaluation, and improvement.